Meningkatkan Kemandirian Belajar Peserta Didik Kelas VII Melalui PBL Dalam PAK dan BP di SMPN 2 Siberut Tengah - Juliasman Satoko; Ansel Joko Prayitno (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Education is currently still believed to be a very effective medium in building independent learning. The learning independence that the author means in this research is related to a condition where students are able to process themselves in making decisions and are responsible for the actions they take. In this research, the author also uses the Problem Based Learning (PBL) learning model. So that the learning process is always related to Problem Based Learning (PBL) learning steps. To achieve the educational goals proclaimed by the government, the author as a Catholic Religious Education teacher wants to take part in it, namely by increasing the learning independence of students in PAK which the author experiences is still very minimal, especially for students who are in the Mentawai Islands Regency and especially class VII students at SMPN 2 Siberut Tengah, with the title class action research :